Electron beam analysis induces Cl vacancy defects in a NaCl thin film. (9th December 2021) - Quertite, Khalid; Enriquez, Hanna; Trcera, Nicolas; Bendounan, Azzedine; Mayne, Andrew J; Dujardin, Gérald; El kenz, Abdallah; Benyoussef, Abdelilah; Dappe, Yannick J; Kara, Abdelkader; Oughaddou, Hamid
Abstract: This work reports on the electron-induced modification of NaCl thin film grown on Ag(110). We show using low energy electron diffraction that electron beam bombardment leads to desorption and formation of Cl vacancy defects on NaCl surface. The topographic structure of these defects is studied using scanning tunneling microscopy (STM) showing the Cl defects as depressions on the NaCl surface. Most of the observed defects are mono-atomic vacancies and are located on flat NaCl terraces. Auger electron spectroscopy confirms the effect of electron exposure on NaCl thin films showing Cl atoms desorption from the surface. Using density functional theory taken into account the van der Waals dispersion interactions, we confirm the observed experimental STM measurements with STM simulation. Furthermore, comparing the adsorption of defect free NaCl and defective NaCl monolayer on Ag(110) surfaces, we found an increase of the adhesion energy and the charge transfer between the NaCl film and the substrate due to the Cl vacancy. In details, the adhesion energy increases between the NaCl film and the metallic Ag substrate from 30.4 meV Å −2 for the NaCl film without Cl vacancy and from 39.5 meV Å −2 for NaCl film with a single Cl vacancy. The charge transfer from the NaCl film to the Ag substrate is enhanced when the vacancy is created, from 0.63e − to 1.25e − .